Lymphoma with skin localization and COVID 19 - a clinical case and review of literature - Maria Moneva-Sakelarieva; Yozlem Kobakova; Spiro Konstantinov; Georgi Momekov; Niya Emilova Semerdzhieva; Stefka Аchkova Ivanova; Ventseslava Petrova Atanasova; Petar Yordanov Atanasov; Maria Stamova Vakrilova Becheva (Pensoft Publishers, 2024)
In this article, we present a clinical case of a 63-year-old patient who was treated in the COVID unit of the Clinic for Internal Diseases of UMBALSM (University General Hospital for Active Care and Emergency Medicine) "N. I. Pirogov" on the occasion of a proven coronavirus infection with a PCR positive test for SARS-CoV2-virus, clinical symptoms of severe coronavirus pneumonia, and with accompanying disease - lymphoma with skin localization, condition after lower right lobectomy, chemotherapy and checkpoint therapy for squamous cell carcinoma of the lung. We also examined the role of the transcription factor NF-kB in the course of the coronavirus infection in a patient with the indicated lymphoproliferative disease and a history of active smoking. We tried to clarify questions such as "Do severe forms of coronavirus infection and the relatively rare disease lymphoma with cutaneous localization have a common pathogenesis?" Is it possible to effectively pharmacotherapeutically influence two, at first glance, so heterogeneous diseases?'' The conclusions drawn can help us to specify certain nosological units as "more vulnerable" to severe forms of COVID19 infection.